Waqf Business Model (WBM): Towards A Sustainable Social Business Model on The Mainstream Economics - Afifi, Abdullah A (IDRIS Darulfunun Institute, 2024)
The Waqf Business Model (WBM) represents an innovative and transformative approach to establishing a sustainable social business model within mainstream economics, rooted in Islamic economic principles. This paper explores the current state of waqf as an alternative model for social business, emphasizing its ability to combine social impact with long-term economic sustainability by preserving assets and generating ongoing revenue. It also advocates for integrating WBM into the mainstream economy to serve as a powerful mechanism for addressing the Sustainable Development Goals (SDGs). The paper highlights the challenges faced by traditional Islamic economic institutions, particularly waqf, which have struggled due to outdated management practices and a conceptual crisis regarding the role of waqf in modern economies. Revitalizing waqf institutions requires enhancing their capabilities and aligning them with contemporary business strategies. Additionally, this paper encourages future research to explore how WBM can be fully integrated into the existing economic ecosystem. In theory, WBM provides a framework for ethical and inclusive economies, while in practice, it has the potential to create self-sustaining institutions that reduce reliance on external aid, offering an innovative solution to global socio-economic challenges by blending sustainable innovation.